2021
DOI: 10.3389/fped.2021.642781
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Molecular Test in Saliva for Detection of COVID-19 in Pediatric Patients With Concurrent Conditions

Abstract: Background: The reference standard for the molecular diagnostic testing for COVID-19 is the use of nasopharyngeal or combined nasopharyngeal and oropharyngeal (NP/OP) swabs. Saliva has been proposed as a minimally invasive specimen whose collection reduces the risks for health care personnel.Objective: To assess the suitability of saliva for COVID-19 diagnosis as a replacement of the reference standard NP/OP swab in the setting of a tertiary care pediatric unit.Study design: A paired study based in the prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…To our knowledge, this study is the largest paediatric study comparing OSS with the established gold standard. The results are in concordance with the few studies performed on children 5 7 9 10 24. A recent study performed in Dubai with 476 children demonstrated a sensitivity even higher (87.7%) than found here; however, the authors used a saliva sample rather than saliva swabs, and the children were older (mean 10.8 years old) 10.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this study is the largest paediatric study comparing OSS with the established gold standard. The results are in concordance with the few studies performed on children 5 7 9 10 24. A recent study performed in Dubai with 476 children demonstrated a sensitivity even higher (87.7%) than found here; however, the authors used a saliva sample rather than saliva swabs, and the children were older (mean 10.8 years old) 10.…”
Section: Discussionsupporting
confidence: 91%
“…We found that OSS RT-PCR could detect some cases that were missed by the NPS RT-PCR; four cases were positive for OSS RT-PCR but negative for NPS RT-PCR, as has been described previously 7–9. Also, three of those four cases had positive serology but were negative for the Ag-RDT.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, it has been previously shown that throat swab specimens might have lower viral loads than nasopharyngeal samples (29), and that nasopharyngeal samples are best at sensitivity detection, especially in early stages of disease and in asymptomatic individuals (30). The non-invasive specimen saliva/sputum also exhibited high sensitivity (87%) and specificity (98%) for the detection of SARS-COV-2 (31), and had similar sensitivity for detecting SARS-CoV-2 with nasopharyngeal samples (32); however, in a pediatric population, the sensibility of the saliva test was not high enough to replace the use of swab for COVID-19 diagnosis (33). In this study, we used respiratory specimens of both throat swab and sputum.…”
Section: Discussionmentioning
confidence: 99%
“…Although small, these studies suggest that the sensitivity of saliva as a paediatric diagnostic sample type is acceptable compared to nasopharyngeal swabs, but not perfect. Interestingly, whilst missing a few cases detected in nasopharyngeal swab samples, SARS-CoV-2 may be additionally detected in some saliva samples where nasopharyngeal swab is negative ( 10 , 11 , 12 ). Interpreting these positive NAT results from saliva samples remains difficult in the absence of a defined gold standard comparator test.…”
mentioning
confidence: 99%